Neurocysticercosis detected by targeted next-generation sequencing of cerebrospinal fluid: a case report - Ren, Xintong; Sun, HuiQin; Cheng, Yanghong; Zhang, Yunzhou; Gao, Daiquan (Frontiers in Neurology, 2025)
The patient, a middle-aged male with a long history of the disease, had experienced recurrent headaches for 26 years and episodic shaking of the right limb with slurred speech for the past month. He was previously diagnosed with cerebral cysticercosis and had shown improvement after anthelmintic treatment. In recent years, he noted a resurgence of headaches. One month prior, he developed right limb shaking and occasional slurred speech. A clinical neurological examination was unremarkable, but cranial MRI and cerebrospinal fluid sequencing confirmed a diagnosis of cerebral cysticercosis. Anthelmintic treatment was administered, resulting in symptom improvement.